1987
DOI: 10.1159/000234233
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Factors Involved in the Regulation of the IgE Synthesis

Abstract: The IgE-potentiating and IgE-suppressive factors share a common structural gene and therefore a common polypeptide chain, and their biologic activities are decided by a post-translational glycosylation process. Under physiological conditions, this process is controlled by two T cell factors, i.e., the glycosylation-enhancing factor (GEF) and glycosylation-inhibiting factor (GIF). GIF is a fragment of phosphorylated lipocortin and has immunosuppressive effects. Repeated injections of this lymphokine into antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It is possible, however, that a combination of specific allergens with non-specific immunopharmacological agents could overcome this problem, and manipulate the cell clones responsible for the synthesis of allergen-specific IgE. Cyclophosphamide and cyclosporin A are drugs now utilized in rheumatology and transplantation immunology, and it is conceivable that immuno-modulatory agents more restricted to the IgE system will be available in future (36). Allergen-specific immunopharmacology will necessitate allergen preparations closely matching the needs of the individual patient, and in this context patient-related allergens might offer a possibility.…”
Section: Rationales For Utilization Of Igg-allergen Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible, however, that a combination of specific allergens with non-specific immunopharmacological agents could overcome this problem, and manipulate the cell clones responsible for the synthesis of allergen-specific IgE. Cyclophosphamide and cyclosporin A are drugs now utilized in rheumatology and transplantation immunology, and it is conceivable that immuno-modulatory agents more restricted to the IgE system will be available in future (36). Allergen-specific immunopharmacology will necessitate allergen preparations closely matching the needs of the individual patient, and in this context patient-related allergens might offer a possibility.…”
Section: Rationales For Utilization Of Igg-allergen Complexesmentioning
confidence: 99%
“…Another example from this field is the concept (borrowed from oncology) of an "allergic bullet", a strongly radiolabelled allergen molecule that destroys the immunocompetent cells by which it is recognized (20). More delicate procedures involve in vitro boosting of T-suppressor lymphocytes (98) or administration of allergen in conjugation with IgE-restricted lymphokines (36) selectively suppressing the synthesis of specific IgE.…”
mentioning
confidence: 99%
“…As I have described characteristics of IgE-BF be fore the last CIA Meeting [6], I shall not go through details. Briefly, (1) IgE-BFconsisted of IgE-potentiating factors (IgE-PF) and IgE-suppressive factors (IgE-SF), and both are derived from FcR+ T cells; (2) the target of the factors appears to be sIgE+ B cells which are committed for IgE-synthesis [7]; (3) using a cloned T cell hybridoma, it was found that the same cells can produce either IgE-SF or IgE-PF under dif ferent environment [8], and (4) gene cloning of IgE-BF indicated that IgE-PF and IgE-SF may share a common polypeptide chain and that their biologic activities are determined during posttranslational glycosylation processes [9].…”
Section: Regulation Of Ige Synthesis By Ige-binding Factors (Ige-bf)mentioning
confidence: 99%
“…It is currently accepted that IgE plays a major role in allergy, and this is probably the reason why so many vi'orks are devoted to the regulation of synthesis of this antibody and to the Fc^ receptors of different affinities present on a variety of cells possibly involved in allergic inflammation [1][2][3][4][5][6][7][8][9].…”
Section: Introduetionmentioning
confidence: 99%
“…
IntroduetionIt is currently accepted that IgE plays a major role in allergy, and this is probably the reason why so many vi'orks are devoted to the regulation of synthesis of this antibody and to the Fc^ receptors of different affinities present on a variety of cells possibly involved in allergic inflammation [1][2][3][4][5][6][7][8][9].TgA is also suspected to play a role in allergy, although this role remains rather obscure. Nevertheless, high serum IgA antibodies were found in some subjects sensitive to ragweed or mite [10][11][12] and in patients presenting with an allergic bronchopulmonary aspergillosis [13][14][15], The same immunoglobulin was demonstrated in the nasal secretions from ragweed and grass-pollen sensitive subjeets as well as in the sputum from asthmatics [12,16,17].
…”
mentioning
confidence: 99%